Penegakan Hukum Terhadap Penyertaan dalam Tindak Pidana Pemurnian atau Pengolahan Emas Tanpa Izin di Kabupaten Indragiri Hulu Berdasarkan Pasal 55 Kitab Undang-Undang Hukum Pidana - Anggreini, Indri; ', Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Article 33 Paragraph (3) of the 1945 Constitution of the Republic of Indonesia states that: "Theearth and water and the natural resources contained therein are controlled by the State and used as much aspossible for the prosperity of the people. Understanding of mining according to Law Number 4 of 2009concerning Mineral and Coal Mining, Article 1 Paragraph (1) mining is a part or all stages of activities inthe framework of research or management of mineral or coal which includes general investigation,exploration, feasibility studies, construction , mining, processing and refining, transportation and sales, andpost-mining activities. Gold mining and refining activities also took place in the Indragiri Hulu Regencyspecifically in Selunak Village, Batang Peranap Subdistrict, besides in Batang Peranap District the samething happened in Peranap Subdistrict and in Kelayang District. The activity was carried out by the peoplewho were around the area and there were even people from other regions. This activity has become alivelihood for the community, but the gold processing and refining activities were carried out withoutpermission, so that in conducting these business activities they did not see the impact that would be causedby their activities.This research is a sociological or empirical research that is the type of research that uses theassumption of the community in finding facts that occur in the field to answer an existing problem. Thisresearch was carried out in the jurisdiction of the Indragiri Hulu Resort Police. While the population andsample are parties related to the problems examined in this study, data sources used, primary data,secondary data, and tertiary data. Data collection techniques in this study with interviews and literaturereview.From the results of the research that the researcher did, it can be concluded, first, LawEnforcement for Participants in Participating in Crimes of Unlicensed Gold Purification and Processing inIndaragiri Hulu Regency Based on Article 55 of the Criminal Code, Indragiri Hulu Regional Police havenot fully enforced the law, because there is still room for perpetrators criminal act. Barriers to LawEnforcement against Participants in Participation in Unlicensed Gold Purification or Processing inIndragiri Hulu Regency are human resources (HR) factors, the difficulty for the investigator in obtainingevidence in the form of letters, documents and other evidence. The efforts made by the Police, here are theefforts that have been made by the Police in law enforcement, the recruitment of human resources needed bythe Police must be done transparently and the employee must have certainty and capability in the Policefield, the mutation system and job rolling must be truly pay attention to the principles of justice and qualityof human resources, increase training for the Police.